2016
DOI: 10.1101/039107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial sequences detected in 99 out of 99 serum samples from Ebola patients

Abstract: Bacterial sequences detected in 99 out of 99 serum samples from Ebola patientsEvolution and clinical manifestations of Ebola virus (EBOV) infection overlap with the pathologic processes that occur in sepsis 1 . Some viruses certainly compromise the immune system, leading to a breach in the integrity of the mucosal epithelial barrier, thus allowing bacterial translocation 2, 3 . Guided by these facts, we wondered if bacteria could be involved in the pathogenesis of some of the septic shock-like symptoms typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There were no blood cultures, tissue cultures, or PCR-based quantitative bacterial studies performed in these protocols. Of note, gram-negative bacteremia has been observed in humans infected with EBOV and it has been hypothesized that this is related to gut translocation [ 5 , 11 , 12 ]. Another limitation of our analysis is that 2/31 (6%) of the NHPs in our cohort were found dead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no blood cultures, tissue cultures, or PCR-based quantitative bacterial studies performed in these protocols. Of note, gram-negative bacteremia has been observed in humans infected with EBOV and it has been hypothesized that this is related to gut translocation [ 5 , 11 , 12 ]. Another limitation of our analysis is that 2/31 (6%) of the NHPs in our cohort were found dead.…”
Section: Discussionmentioning
confidence: 99%
“…The use of empiric antibiotics seems to be supported by Kreuels et al [ 5 ] who reported that their critically ill Ebola patient experienced intestinal dysmotility and sepsis presumably due to translocation of a multi-drug resistant (MDR) gram-negative bacillus from the GI tract. A recent study demonstrated bacterial sequences in 99/99 (100%) serum samples examined from Ebola patients [ 11 ]. Furthermore, Carroll et al found that the majority of their cohort of 179 subjects that tested qRT-PCR positive for Ebola virus (EBOV) had evidence of bacterial translocation across the gut [ 12 ].…”
Section: Introductionmentioning
confidence: 99%